Doctor shopping behaviour and its predisposing factors amongst dermatology patients - Nizafaziasyida Fauzee Andylim,; Adawiyah Jamil,; Norazirah Md Nor,; Muhammad Adil Zainal Abidin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Doctor shopping increases health economic burden and morbidities. Its prevalence and predisposing factors have to be identified in order to formulate preventive measures. We aimed to determine the prevalence of doctor shopping, its reasons and predisposing factors by conducting a cross sectional study of new patients at the Dermatology Clinic, Universiti Kebangsaan Malaysia Medical Centre (UKMMC). Doctor shopping was defined as having consultation with ≥3 healthcare providers without a referral for the same illness prior to the patients’ visit to UKMMC. Reasons and contributing factors were classified as disease, healthcare provider, logistic and cost related. Data was collected by a face to face interview. Dermatology Life Quality Index (DLQI) questionnaire determined disease impact on the patients. A total of 58 (55.8%) female and 46 (44.2%) male patients participated. Referral was patient-initiated in 51.9% while 40.4% were doctor shopping. Age, gender, ethnicity, income, occupation and type of health finance provider were not associated with this behaviour. About 95% doctor shopped due to disease factors: searching for a cure (95.2%), lack of improvement (88.1%), worsening disease (50.0%), dissatisfaction with treatment (31.0%), seeking other opinions (26.2%) and exploring treatment options (26.2%). Impaired DLQI (OR 1.17; 95% CI 1.08,1.38), p 0.04, and disease related factors (OR 6.57; 95% CI 1.52, 7.72), p 0.041 were significant independent risk factors. Doctor shopping is very common among our patients. Reasons and predisposing factors are predominantly disease related. Patient education and counselling is important in management of dermatological diseases to prevent doctor shopping.